The relationship between proficiency in multiple languages and working memory: a study of multilingual advantages in South Africa. - Espi-Sanchis, Gabriel (My University, 2018)
This study explores the relationship between multilingualism and working memory. Multilingual advantages in various executive functions have been established, but little is known about whether multilingual advantages extend to working memory capacity and functioning, or about the effect of speaking more than two languages. In a sample of 189 multilingual young adults in South Africa, this study used a multiple regression design in which numerous aspects of multilingualism - balance in proficiency across and within languages, the age of acquisition of additional languages, and speaking a third language - could be compared with one another while controlling for socio-economic status. Four aspects of working memory (verbal storage, verbal processing, visuospatial storage and visuospatial processing), measured using the Automated Working Memory Assessment (Alloway, 2007), acted as the dependent variables in respective regressions while independent variables measuring multilingualism, including the continuous measures of balance in reading, speaking and understanding proficiency across languages, were based on self-report information from the Language Experience and Proficiency Questionnaire (LEAPQ; Marian, Blumenfeld, & Kaushanskaya, 2007). Balance in proficiency emerged as a strong predictor of the verbal processing component of working memory, while no aspect of multilingualism significantly predicted visuospatial working memory. Combined with other results, this finding suggested that the effect of multilingualism on working memory may not follow the pattern observed in other tasks where multilinguals are advantaged in domaingeneral executive functions (like inhibitory control) but disadvantaged in linguistic tasks. Multilinguals’ experience in storing and processing linguistic information may lead to advantages (possibly through managing attention) that are specific to this kind of information. Keywords: bilingual advantage, executive function, multilingual advantage, trilingualism, working memory !
A research project submitted in partial fulfilment of the requirements for the degree of MA in Psychology in the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 20 June 2018
Keywords: Education, Bilingual--South Africa; Multilingualism--South Africa